Microstructure and Crystallographic Preferred Orientations of an Azimuthally Oriented Ice Core from a Lateral Shear Margin: Priestley Glacier, Antarctica - Thomas, Rilee E.; Negrini, Marianne; Prior, David J.; Mulvaney, Robert; Still, Holly; Bowman, M. Hamish; Craw, Lisa; Fan, Sheng; Hubbard, Bryn; Hulbe, Christina; Kim, Daeyeong; Lutz, Franz (Frontiers in Earth Science, 2021)
A 58 m long azimuthally oriented ice core has been collected from the floating lateral sinistral shear margin of the lower Priestley Glacier, Terra Nova Bay, Antarctica. The crystallographic preferred orientations (CPO) and microstructures are described in order to correlate the geometry of anisotropy with constrained large-scale kinematics. Cryogenic Electron Backscatter Diffraction analysis shows a very strong fabric (c-axis primary eigenvalue ~0.9) with c-axes aligned horizontally sub-perpendicular to flow, rotating nearly 40° clockwise (looking down) to the pole to shear throughout the core. The c-axis maximum is sub-perpendicular to vertical layers, with the pole to layering always clockwise of the c-axes. Priestley ice microstructures are defined by largely sub-polygonal grains and constant mean grain sizes with depth. Grain long axis shape preferred orientations (SPO) are almost always 1-20° clockwise of the c-axis maximum. A minor proportion of ‘oddly’ oriented grains that are distinct from the main c-axis maximum, are present in some samples. These have horizontal c-axes rotated clockwise from the primary c-axis maximum and may define a weaker secondary maximum up to 30° clockwise of the primary maximum. Intragranular misorientations are measured along the core, and although the statistics are weak, this could suggest recrystallisation by subgrain rotation to occur. These microstructures suggest subgrain rotation (SGR) and recrystallization by grain boundary migration recrystallisation (GBM) are active in the Priestley Glacier shear margin. Vorticity analysis based on intragranular distortion indicates a vertical axis of rotation in the shear margin. The variability in c-axis maximum orientation with depth indicates the structural heterogeneity of the Priestley Glacier shear margin occurs at the meter to tens of meters scale. We suggest that CPO rotations could relate to rigid rotation of blocks of ice within the glacial shear margin. Rotation either post-dates CPO and SPO development or is occurring faster than CPO evolution can respond to a change in kinematics.